Circulating Salusin-beta Levels in Various Open-Angle Glaucoma Types - Turgut, Burak; Mercan, Kadir; Ilhan, Nevin; Demir, Nesrin; Catak, Onur (Gazi Eye Foundation, 2021)
Purpose: To evaluate the levels of salusin-beta (?-Sal) in the serum in patients with open-angle glaucoma. Materials and Methods: This pilot work was designed as an institutional controlled comparative clinical study. The serum ?-Sal levels of age and sex-matched 20 healthy volunteers as controls (Group 1), 15 patients with normal-tension glaucoma (NTG) (Group 2), 18 patients with pseudoexfoliative glaucoma (PXG) (Group 3) and 26 patients with primary open-angle glaucoma (POAG) (Group 4) were measured with the enzyme-linked immunosorbent assay (ELISA) method. Results: There was no statistically significant difference concerning age and gender among the groups (p>0. 05). The mean serum ?-Sal levels in Group 1, Group 2, Group 3 and Group 4 were 4977.02±3741.44 pg/mL; 1086.57±253.41 pg/mL; 1044.98±268.80 pg/mL and 868.32±181.78 pg/mL, respectively. Although the mean ?-Sal levels in all glaucoma groups seem numerically lower than the control group, there was no statistically significant difference between the serum ?-Sal concentrations of the study groups (p>0.05). Conclusion: These findings suggest that serum salusin-? levels are not different among various open-angle glaucoma types. However, theoretically, ?-Sal may contribute to the pathogenesis of glaucoma and may play a neuroprotective hormone in glaucoma. Further studies with large patient population are required to say whether ?-Sal plays a role in the pathogenesis of glaucomatous optic neuropathy. © 2021, Gazi Eye Foundation. All rights reserved.
Keywords: Open-angle glaucoma; Salusin beta; Serum level